Improvement In Physical Fitness Index, Vo2 Max Score And Hemoglobin Level With Diet And Nutrition Intervention (Applied Biological Research, 2019)
The physical fitness index measures the physical fitness for muscular work and  he ability to recover from the work. The study was undertaken to assess the  physical fitness index and aerobic capacity by using Harvard step test and  evaluate hemoglobin level of moderately anemic (8-10.9 mg dL-1) adolescent  girls (10-18 yr). Intervention was given 90 moderately anemic adolescent girls  divided into three groups for a period of 4 months. Each group constituted 30  girls. Group-I was given iron-rich diet as well as nutrition counseling and  group-II received only nutrition counseling. Group-III formed the control  group i.e. no intervention of any type was provided to them. The scores of  physical fitness index showed the positive impact of intervention on  experimental groups. Nutrition intervention improved their physical fitness  index and Vo2 max scores level to good and excellent fitness. Nutrition and  dietary intervention improved their Hb level. The study concluded that  physical fitness index, VO2 max scores and level of hemoglobin improved with  diet as well as nutrition counseling nutritional intervention.
Keywords: Adolescent girls; aerobic capacity; hemoglobin; intervention; physical fitness index